Influence of socio-affective factors on quality of life in women diagnosed with fibromyalgia - Ortega-Martínez, Ana Raquel; Grande-Gascón, María Luisa; Calero-García, María José (Frontiers in Psychology, 2023)
Introduction Fibromyalgia is a disease that involves chronic pain, with high prevalence in the female population and great impact on the bio-psycho-social sphere of people affected by it. However, few studies have analyzed the possible influence of socio-affective factors on the quality of life of people who suffer from this disease. Objective The aim of this study was to determine the relationships between the impact of this disease on the lives of people with fibromyalgia and these variables. Specifically, we analyzed the quality of partner relationship, perceived loneliness, life satisfaction, and perceived socio-family situation. Method A descriptive-correlational cross-sectional design was used. The sample consisted of 69 women diagnosed with fibromyalgia. The participants completed different questionnaires that measured their happiness, satisfaction with life, perceived loneliness, quality of partner relationship, socio-family valuation, and the impact of fibromyalgia. Results The quality of partner relationship, perceived loneliness and socio-family valuation seem to be good predictors of subjective happiness, life satisfaction, and the impact that fibromyalgia has on people’s lives, in the sense that the more positive the valuation of the couple relationship and of the socio-family situation, and the lower the perceived loneliness, people feel happier, more satisfied with their lives and the lower the impact that fibromyalgia has on their lives. Conclusion The 50% of satisfaction with life can be explained from the scores obtained in perceived loneliness and the quality of partner relationship. In this sense, perceived loneliness was a good predictor of the impact of fibromyalgia on the lives of these patients.